Analysis of Giouan Battista Bellaso's cipher challenges of 1555. Issue 5 (3rd September 2018) - Biermann, Norbert
ABSTRACT: In his book, Noui et singolari modi di cifrare, Giouan Battista Bellaso presented to his readers three challenge ciphertexts. Two of them are based on a polyalphabetic cipher with a mixed primary reciprocal alphabet and a long key, whereas the third one uses four independent homophonic substitution alphabets that change after each word. A successful approach to solving these ciphers, to which Bellaso gave the name "terzo modo" and "quarto modo, " performs a simulated annealing attack directly on the primary alphabet, respectively the four homophonic alphabets at once. This article focuses on the various applied fitness functions. The solutions for the ciphertexts are given and finally discussed, with a view toward the possibility of a hidden message within the plaintexts.